Hot-carrier-induced current capability degradation and optimization for lateral IGBT on thick SOI substrate. (July 2018) - Zhang, Chunwei; Li, Yang; Yue, Wenjing; Fu, Xiaoqian; Li, Zhiming
Highlights: The hot-carrier-induced I sat degradation of SOI-LIGBT is investigated. It is found that I sat degradation is worse than I lin degradtion for SOI-LIGBT. A novel SOI-LIGBT structure with optimized HCI reliability is proposed. Abstract: In this paper, the hot-carrier-induced current capability degradation of a 600 V lateral insulated gate bipolar transistor (LIGBT) on thick silicon on insulator (SOI) substrate is investigated. Our experiments found that, for the SOI-LIGBT, the worst stress condition is the maximum gate voltage ( V gmax ) condition and the current degradation is dominated by the damages in the channel region under the V gmax stress condition. However, further analyses show that the influence of channel region damages on the collector current degradation increases with the increase of measured collector voltage and is maximum in the current saturation region. Therefore, in our opinion, the hot-carrier-induced current capability degradation of the SOI-LIGBT should be evaluated by the degradation of saturation current under the V gmax stress condition. In addition, a novel SOI-LIGBT structure with an external p-type region was also proposed, which can alleviate the damage in the channel region by reducing the lateral electric field peak. Our experimental results demonstrate that the proposed structure could optimize the hot-carrier reliability effectively with the other characteristics maintained.